The factors influence training needs for halal logistics industry in Malaysia / Khazizul Maulod Pahim - Pahim, Khazizul Maulod (2012)
Halal product has a huge potential to expand globally. The Islamic community have raised about 2 billion consumers and it is estimated that total expenditure on the logistics operation is 5 to 10 per cent of the total income. Therefore, the logistics companies all over the world are keen to grab this opportunities on massive potential of the Halal industries. As a fast expanding business, the Halal industry is now estimated for around USD 2.1 trillion. The attention and demand for Halal certified services and products continue to rise throughout the world because Halal is not only about religious obligations but also concern the powerful market demand forces whereby the demand for Halal products keeps on rising and it is not just consumed by the Muslims but also consumed by the non-Muslims all over the world. Halal is not only concerned about the way to slaughter animal and food preparation, but also focuses on where the resources and materials of the product come from. Halal products can turn to Haram at any time through the logistics process and here comes the importance of the training needs in Halal industry in Malaysia. The lack of trained workforce in Halal industry can cause a sense of doubt of the Halal product the market has to offer. Therefore, this thesis intends to achieve the following objectives namely (1) To determine the current state of Halal logistics industry in Malaysia (2) To identify the factors influence the training needs in Halal logistics (3) To identify the types of institutions and types of training for the Halal logistics industry offered in Malaysia (4) To make recommendations and propose measures and action plans to enhance training to meet the needs for the Halal logistics industry. This study relies heavily on disclosed and published materials such as logistics firms annual reports, journals, newspapers and business magazines articles, published reports produced by consultants, special studies and reports commissioned by the Malaysian Government. In addition, this study also relies on information provided by the logistics/supply chain users, logistics providers, industry experts and practitioners by way of survey and interviews. The quantitative data provided a sense of how most of the 3PL handled the Halal product starting from the first process in the value chain to the end of the process. This provided a general level of 3PL knowledge and awareness towards the Halal logistics in order to make sure the Halalness of the product.